Perancangan dan Implementasi Aplikasi Toko Koperasi Sekolah berbasis Website dengan Memanfaatkan Payment Gateway Midtrans (Studi Kasus: SMK Negeri Temayang) - Ayezha Halidar Putri Irwanda; Bayu Rahayudi; Dwija Wisnu Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Cooperatives at SMK Negeri Temayang are spaces that are usually used by students in conducting transactions between students and cooperative officers. Currently, the SMK Negerti Temayang cooperative serves students in making purchase transactions for food, beverages, and goods still using the conventional system. Problems that arise in making purchase transactions at cooperative stores during recess hours result in students and other visitors not being neatly arranged in queues and may be crowded when they are about to buy, making it difficult to process orders made at about the same time. In addition, it causes cooperative managers to experience obstacles and errors in summing the results of sales transactions in cooperative stores. The solution to this problem was designed and built a menu and goods ordering system, namely, "Application of the School Cooperative Store SMKN Temayang by utilizing the Midtrans Payment Gateway" so that there are no queues and resulting in crowding when the rest hour arrives. The payment method is carried out by means of a midtrans payment gateway that can handle transaction problems in cooperative stores so that transactions are made more efficiently. To build this application, a description and planning for functional and non-functional needs in the application is needed, namely utilizing the UML scheme. Application development is straightforward by using Rapid Application Development (RAD) with the programming languages PHP, DBMS MySQL, and laravel. This test is carried out after the implementation step is completed, namely blackbox testing gets 100% valid success which means the system runs well, compatibility testing gets compatible results so it can run in different browsers, and system usability testing is carried out with 5 respondents. The usability test results in an average value or final result of 82 with acceptable conclusions on the aspect of acceptability ranges, with an excellent category with a scale grade of B.